Rational Design of Hyaluronic Acid-Based Copolymer-Mixed Micelle in Combination PD-L1 Immune Checkpoint Blockade for Enhanced Chemo-Immunotherapy of Melanoma - Zhou, Chaopei; Dong, Xiuxiu; Song, Chunxiang; Cui, Shuang; Chen, Tiantian; Zhang, Daji; Zhao, Xiuli; Yang, Chunrong (Frontiers in Bioengineering and Biotechnology, 2021)
The application of combinational therapy break the limitation of monotherapy and achieve better clinical benefit for tumor therapy. Herein, a hyaluronic acid/Pluronic F68-based copolymer mixed micelle was constructed for targeted delivery of chemotherapeutical agent docetaxel (PHDM) in combination with programmed cell death ligand-1(PD-L1) antibody. When PHDM+anti-PDL1 was injected into blood system, PHDM could accumulate into tumor sites and target tumor cells via CD44 mediated endocytosis and possess tumor chemotherapy. While anti-PDL1 could target PD-L1 protein expressed on surface of tumor cells to immune checkpoint blockade characteristic for tumor immunotherapy. This strategy could not only directly kill tumor cells but also improve CD8+ T cell level and facilitate effector cytokines release. In conclusion, the rational designed PHDM+anti-PDL1 therapy strategy creates a new way for tumor immune-chemotherapy.